2022
DOI: 10.7150/ijbs.66480
|View full text |Cite
|
Sign up to set email alerts
|

RBMS2 Chemosensitizes Breast Cancer Cells to Doxorubicin by Regulating BMF Expression

Abstract: Chemoresistance is closely related to the therapeutic effect and prognosis in breast cancer patients. Increasing evidences demonstrated that RNA binding proteins (RBPs) have notable roles in regulating cancer cell proliferation, metastasis and chemotherapeutic sensitivity. RNA binding motif single stranded interacting protein 2 (RBMS2), an RBP, has been considered to be a tumor suppressor in several cancers. However, its role of doxorubicin sensitivity in breast cancer patients has not yet been fully revealed.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“… 40 In the presence of Adriamycin, upregulated RBMS2 in breast cancer cells promotes BMF expression and increases expression of cleaved caspase-3, cleaved caspase-9, and poly ADP-ribose polymerase to exacerbate apoptosis. 43 In addition, knockdown of Eomes in human colon cancer cells increases BMF expression, which is accompanied by increased levels of cleaved caspase-3 and cleaved caspase-7, and decreased expression of survivin, leading to apoptosis. 44 In fact, our research showed that overexpression of BMF in CSE-treated A549 cells increased the expression of pro-apoptotic proteins (p53, caspase-3, and caspase-7) and inhibited the expression of anti-apoptotic proteins (Bcl-2 and survivin) to exacerbate apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“… 40 In the presence of Adriamycin, upregulated RBMS2 in breast cancer cells promotes BMF expression and increases expression of cleaved caspase-3, cleaved caspase-9, and poly ADP-ribose polymerase to exacerbate apoptosis. 43 In addition, knockdown of Eomes in human colon cancer cells increases BMF expression, which is accompanied by increased levels of cleaved caspase-3 and cleaved caspase-7, and decreased expression of survivin, leading to apoptosis. 44 In fact, our research showed that overexpression of BMF in CSE-treated A549 cells increased the expression of pro-apoptotic proteins (p53, caspase-3, and caspase-7) and inhibited the expression of anti-apoptotic proteins (Bcl-2 and survivin) to exacerbate apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…These findings highlight the therapeutic potential of RBMS2 in ccRCC. Indeed, RBMS2 was reported to chemosensitize breast cancer cells to doxorubicin, implying its therapeutic potential [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…Investigations into different types of cancers such as lung cancer, gastric cancer, and hepatocellular carcinoma have reported a downregulation of RBMS2. This diminished expression of RBMS2 is seen to contribute to the initiation and progression of these cancers, thereby establishing a link between RBMS2 downregulation and oncogenesis [ 3 ]. However, the role of RBMS2 in kidney renal clear cell carcinoma (ccRCC), which is the most prevalent subtype of kidney cancer, has not been thoroughly explored.…”
Section: Introductionmentioning
confidence: 99%
“…Upregulation of RNA binding motif single stranded interacting protein 2 enhances the sensitivity of BC cells to doxorubicin, while inhibition of this RBP has an opposite trend. Motif single stranded interacting protein 2 positively regulates the expression of Bcl-2 modifier and increases the expression of cleaved caspase 3, cleaved caspase 9 and poly (ADP-ribose) polymerase which in turn contributes to doxorubicin sensitivity [64]. Epirubicin is another anthracycline agent widely used for BC treatment.…”
Section: Rbps Regulate Chemotherapy Resistance Of Bcmentioning
confidence: 99%